Exploring the structural aspects of alanine racemase enzyme for antitubercular drug discovery – a computational approach - Jayaram, Unni; Parthan Anilkumar; Fathima Rifana Yousuf; Graceson Jose (Journal of Applied Pharmaceutical Research, 2025)
Background: Tuberculosis (TB) is a communicable disease that is a significant cause of ill health and one of the leading causes of death worldwide. The current antibiotics have been pivotal in managing TB to a greater extent. Still, the issue of antitubercular drug resistance is indeed a matter of concern and requires effective drug discovery strategies targeting less explored targets. One of the less explored but promising antitubercular targets, Alanine racemase (AlaR), a prokaryotic enzyme providing the essential peptidoglycan precursor D-alanine (D-Ala) in bacterial cell wall synthesis, is an attractive target for antitubercular drug discovery. Objective: The current study aims to explore the available protein targets of the AlaR enzyme in Mycobacterium tuberculosis and to understand the structural aspects to be followed in designing inhibitors for them. Methodology: As a part of the study, the crystal structure of the alanine racemase enzyme from Mycobacterium tuberculosis was subjected to computational studies using the Schrodinger drug design suite. The significant protocols followed involved protein preparation and fragment-based drug design studies. Results and discussion: The in-silico data suggested that substituted pteridine derivatives, which impart stable interaction at the active site of the alanine racemase enzyme, may be the potential lead moiety for drug design. Conclusion: Although the preliminary screening suggests that the pteridine ring system may be a promising lead, detailed in silico studies must be carried out, such as molecular mechanic generalized born surface area (MM-GBSA), density functional theory (DFT) studies, induced fit docking, molecular dynamics, etc. for further authentication. For effective correlation, detailed in vivo studies on AlaR enzyme inhibition can be carried out from a future perspective.